The Many and the One : Religious and Secular Perspectives on Ethical Pluralism in the Modern World - Strong, Tracy B.; Madsen, Richard, 1941- (Book collections on Project MUSE., 2003)
The war on terrorism, say America's leaders, is a war of Good versus Evil. But in the minds of the perpetrators, the September 11 attacks on New York and Washington were presumably justified as ethically good acts against American evil. Is such polarization leading to a violent "clash of civilizations" or can differences between ethical systems be reconciled through rational dialogue? This book provides an extraordinary resource for thinking clearly about the diverse ways in which humans see good and evil. In nine essays and responses, leading thinkers ask how ethical pluralism can be understo.